Morphometric efficacy evaluation of acne treatment with systemic isotretinoin in the form of LIDOSE - M. L. Abdukhalikova; I. O. Malova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Objective. Evaluation of changes of morphometric skin indicators of patients with moderate severity of acne in the course of treatment with systemic isotretinoin in the LIDOSE form. Materials and methods. 30 patients have been under study in the course of isotretinoin therapy ( LIDOSE form) with the dosage of 0.6-0.8 mg/kg per day till the course dose was reached 100-120 mg per kg of the body mass. Control group comprised 30 apparently healthy people. Results. The research conducted has revealed a high efficacy and tolerance of the therapy, and a valid positive tendency of changes in morphometric skin indicators has also been traced in the course of treatment. Conclusion. The conducted research has indicated that isotretinoin LIDOSE form has a positive effect on pathogenic mechanisms acne.